The Effect of Patient Condition Information Education on the Anxiety of Families of Critically Ill Patients in the ICU - Elisa Indriani; Erna Safariyah; Mustofa Saepul Alamsah; Azhar Zulkarnain Alamsyah (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2026)
Background: Anxiety in families of critically ill patients in the ICU often arises due to a lack of information about the patient's condition. Purpose: To determine the effect of education about the patient's condition on the anxiety levels of families of critically ill patients in the ICU at RSUD Jampang Kulon. Method: A quasi-experimental study with a pretest-posttest control group design. A total of 46 family members were divided into intervention and control groups, each consisting of 23 participants. Anxiety was measured using the Zung Self-Rating Anxiety Scale (ZSAS) before and after the education. The intervention group received structured education, while the control group received standard information. Analysis technique: Data were analyzed using the Wilcoxon and Mann-Whitney tests to examine differences in anxiety levels within and between groups. Results: There was a significant decrease in anxiety scores in the intervention group (p=0.001), whereas the control group showed no significant changes. Most family members in the intervention group shifted from moderate to mild anxiety after the education. Conclusion: Education about the patient's condition effectively reduces anxiety in families of critically ill patients in the ICU at RSUD Jampang Kulon and is recommended as a standard procedure in ICU care.